1997
DOI: 10.1177/088626097012004002
|View full text |Cite
|
Sign up to set email alerts
|

System Intervention Trauma to Child Sexual Abuse Victims Following Disclosure

Abstract: This study attempts to discover if further traumatization occurs to sexually abused children through societal system interventions. The Traumagenic Model, developed by David Finkelhor, which explains the dynamics of trauma in child sexual abuse, was employed as the theoretical framework to understand how societal system interventions can produce or reinforce the previous trauma from sexual abuse. Ninety sexually abused children ages 9 to 19 were selected from three counties that have contrasting societal syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
6

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 9 publications
2
42
0
6
Order By: Relevance
“…Of those children who disclose their sexual abuse, available data suggest most (41.8-57%) make their initial disclosure to a parent or parent-fi gure (Berliner & Conte, 1995;Gomes-Schwartz et al, 1990;Lamb & Edgar-Smith, 1994;Lynch et al, 1993;Roesler & Wind, 1994). Findings of one study revealed that children were about as likely to disclose to a parent (29%) as they were to a friend (27%) (Henry, 1994).…”
Section: Latency To Disclosurementioning
confidence: 99%
“…Of those children who disclose their sexual abuse, available data suggest most (41.8-57%) make their initial disclosure to a parent or parent-fi gure (Berliner & Conte, 1995;Gomes-Schwartz et al, 1990;Lamb & Edgar-Smith, 1994;Lynch et al, 1993;Roesler & Wind, 1994). Findings of one study revealed that children were about as likely to disclose to a parent (29%) as they were to a friend (27%) (Henry, 1994).…”
Section: Latency To Disclosurementioning
confidence: 99%
“…En contrepartie, d'autres études n'ont pas relevé d'impact négatif associé au fait de témoigner (Henry, 1997 ;Mudaly et Goddard, 2006 ;Runyan, Everson, Edelsohn, Hunter et Coulter, 1988 ;Tedesco et Schnell, 1987). À titre d'exemple, Henry (1997) a évalué les réactions traumatiques (Trauma Symptom Checklist ; Briere, 1989) d'un groupe de 90 jeunes victimes d'agression sexuelle ayant été impliqués soit à la chambre de la jeunesse ou à la chambre criminelle.…”
Section: Les Conséquences Associées à L'implication Judiciaireunclassified
“…Toutefois, 38 % jugeaient l'expérience comme ayant été négative et 48 % comme étant réparatrice. Les résultats indiquent que des démarches assurant une préparation, de l'encadrement et du soutien peuvent aider l'enfant dans cette épreuve (Henry, 1997). Pour leur part, Runyan et ses collègues (1988) ont évalué le degré de détresse psychologique associé au fait de témoigner chez un groupe d'enfants et d'adolescents victimes d'agression sexuelle.…”
Section: Les Conséquences Associées à L'implication Judiciaireunclassified
See 1 more Smart Citation
“…Los análisis demostraron que el apoyo social amortiguaba el desarrollo de TEP, a través especialmente del apoyo de autoestima y de evaluación. Los profesionales e investigadores del ASI han planteado algunos interrogantes sobre el posible impacto que la intervención del sistema puede tener en las vidas de estos niños (p.e., Henry, 1997). La investigación y consiguiente intervención en un caso de abuso sexual conlleva la implicación en el mismo de diversos organismos (servicios sociales de protección infantil, policía judicial, juzgados de menores, juzgados de lo penal), cada uno con sus objetivos específicos.…”
Section: Factores Situacionalesunclassified